2022
DOI: 10.1177/00031348221114034
|View full text |Cite
|
Sign up to set email alerts
|

Negative Lymph Node Is an Independent Prognostic Factor for Stage III Gastric Cancer Patients After Curative Gastrectomy: A Surveillance, Epidemiology, and End Results-Based Study

Abstract: Background Negative lymph node (NLN)’ s prognostic impact on stage III gastric cancer (GC) patients after curative gastrectomy has not been rigorously studied. We aimed to explore the relationship between NLNs count and outcomes of stage III GC patients. Methods We retrospectively investigated stage III gastric cancer cases between 2008 and 2018 from Surveillance, Epidemiology, and End Results (SEER) database. Variables were compared by chi2 test. Kaplan-Meier methods and COX proportional hazard models were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Recently, many studies on ELNs have mainly focused on precise postoperative staging and prognosis and found that the prognosis of GC was further improved with the increase in the number of ELNs (13)(14)(15), which means that the probability of clinical cure would also further increase. One reason for this was that ELNs decreased N stage migration after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies on ELNs have mainly focused on precise postoperative staging and prognosis and found that the prognosis of GC was further improved with the increase in the number of ELNs (13)(14)(15), which means that the probability of clinical cure would also further increase. One reason for this was that ELNs decreased N stage migration after surgery.…”
Section: Discussionmentioning
confidence: 99%